Oral batyl alcohol supplementation rescues decreased cardiac conduction in ether phospholipid-deficient mice - Todt, Hannes; Dorninger, Fabian; Rothauer, Peter J.; Fischer, Claus M.; Schranz, Michael; Brügger, Britta; Lüchtenborg, Christian; Ebner, Janine; Hilber, Karlheinz; Koenig, Xaver; Erdem, Fatma A.; Gawali, Vaibhavkumar S.; et al. (Journal of inherited metabolic disease, 2020)
Plasmalogens (Pls) are a class of membrane phospholipids which serve a number of essential biological functions. Deficiency of Pls is associated with common disorders such as Alzheimer's disease or ischemic heart disease. A complete lack of Pls due to genetically determined defective biosynthesis gives rise to rhizomelic chondrodysplasia punctata (RCDP), characterized by a number of severe disabling pathologic features and death in early childhood. Frequent cardiac manifestations of RCDP include septal defects, mitral valve prolapse, and patent ductus arteriosus. In a mouse model of RCDP, reduced nerve conduction velocity was partially rescued by dietary oral supplementation of the Pls precursor batyl alcohol (BA). Here, we examine the impact of Pls deficiency on cardiac impulse conduction in a similar mouse model (GnpatKO). In-vivo electrocardiographic recordings showed that the duration of the QRS complex was significantly longer inGnpatKO mice than in age- and sex-matched wild-type animals, indicative of reduced cardiac conduction velocity. Oral supplementation of BA for 2 months resulted in normalization of cardiac Pls levels and of the QRS duration inGnpatKO mice but not in untreated animals. BA treatment had no effect on the QRS duration in age-matched wild-type mice. These data suggest that Pls deficiency is associated with increased ventricular conduction time which can be rescued by oral BA supplementation.